Law Enforcement Against Illegal Fishing Crimes in Maluku Waters - Meliezer, Stevanno; Lewerissa, Yanti Amelia; Saimima, Judy Marria (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The waters of Maluku are often the main target of Illegal Fishing crimes. The problem in this writing is what factors cause the development of illegal fishing crimes in Maluku waters and how to enforce the law against illegal fishing crimes that occur in Maluku waters.Purposes of the Research: The purpose of this writing is to study and analyze the factors that cause and enforce the law against illegal fishing crimes in Maluku waters.Methods of the Research: The research method used is empirical juridical, the data sources used are primary data and secondary data. Data collection techniques through observation, interviews and literature studies. Qualitative data analysis techniques.Findings of the Research: The results of the study show that the Factors Influencing the Development of Illegal Fishing Crimes in Maluku Waters are upwelling conditions around the Banda Sea and the sea; the geographical location of the Maluku Islands which has an impact on the vulnerability of control and connectivity; coral reef ecosystems, mangroves and seagrass beds that are still good in Maluku waters; lack of human resources for law enforcement officers and fishermen; lack of supporting facilities/facilities; lack of budget; lack of supervision; weak regulations; and lack of community participation. Law Enforcement against Illegal Fishing Crimes in Maluku Waters is influenced by legal factors/statutes; law enforcement officers; supporting facilities/facilities; society and culture.